SOR Theory in Chatbot Services to Increase Repurchase Intention - Fadhly, Hafiz; Kurniawati, Kurniawati; Masnita, Yolanda (SIMAK, 2024)
The Indonesian banking industry is currently undergoing rapid digital transformation, with the adoption of new technologies such as Artificial Intelligence (AI) to enhance customer service and operational efficiency. One interesting application of AI is chatbot services, computer programs that can simulate direct conversations with customers. AI chatbots offer various benefits to the banking industry, such as 24-hour customer service. However, there is limited research evaluating the impact of AI marketing activities through chatbots on repurchase intention in the Indonesian banking sector. This study analyzes the influence of AI marketing activities through AI chatbots on repurchase intention of banking services, with Word of Mouth (WOM) as a mediating variable. This study provides new insights into the impact of AI marketing activities on brand experience and customer repurchase intention. Using a quantitative method with a questionnaire on 300 bank customers. Banks should increase the use of AI and chatbots to increase repurchase intention through WOM.